Agonist vs Antagonist Behavior of δ Opioid Peptides Containing Novel Phenylalanine Analogues in Place of Tyr(1) - Berezowska, Irena (2009)
The novel phenylalanine analogues 4'-[N-((4'-phenyl)-phenethyl)carboxamido]phenylalanine (Bcp) and 2',6'-dimethyl-4'-[N-((4'-phenyl)-phenethyl)carboxamido]phenylalanine (Dbcp) were substituted for Tyr(1) in the δ opioid antagonist TIPP (H-Tyr-Tic-Phe-Phe-OH; Tic = tetrahydroisoquinoline-3-carboxylic acid). Unexpectedly, [Bcp(1)]TIPP was a potent, selective δ opioid agonist, whereas [Dbcp(1)]TIPP retained high δ antagonist activity. Receptor docking studies indicated similar binding modes for the two peptides, except for the biphenylethyl moiety which occupied distinct receptor subsites. The dipeptide H-Dbcp-Tic-OH was a highly selective δ antagonist with subnanomolar δ receptor affinity.